(untitled) (Journal of Plant Disease Sciences, 2020)
Coffee is one the most traded commodity next to petroleum in the world. By the early eighteenth century, coffee commodity chains spread across the world, linking consumers in Europe with producers in Africa, Asia and Latin America. Now adays, coffee is commercially produced in more than 70 countries and the world drinks over 3 million cups a day. The annual revenue of the coffee industry is estimated to exceed 200 billion US dollars. Around 25 million farming households depend on coffee for their livelihood. The history of coffee cultivation in India goes back to 16th century, when the saint Baba Budan introduced the coffee to India and planted in the hills of Chikkamagaluru District, Karnataka state. At present, apart from Karnataka, the coffee is grown in Kerala, Tamil Nadu, Andhra Pradesh, Odisha and North-Eastern states comprising of totally 4,59,895 ha with a total production of 3,19,500 MT (Anonymous, 2019).